Opinions of NKU Faculty of Medicine Intern and Resident Doctors on Distance Medicine Education During the COVID-19 Pandemic Period - Eda ÇELİK GÜZEL; Büşra DURSUN; Aydan ÇEVİK VAROL; Gülsel AYAZ; Birol TOPÇU (Namık Kemal Tıp Dergisi)
Aim: Throughout world history, people in the pandemic have not only been in danger of their physical health but also seriously affected their mental health. To prevent the spread of the virus during the COVID-19 pandemic, the Council of Higher Education of our country has closed schools and conducted education and training via online education. Therefore, the anxiety, uncertainty and closure of schools by the epidemic caused anxiety. The aim of our study; The effect of the COVID-19 pandemic on medical faculty student education is to evaluate the satisfaction of students from distance education applications. Materials and Methods: Our study is a cross-sectional descriptive type and was conducted on 321 students studying in the 4th, 5th and 6th grades Tekirdağ Namık Kemal University Faculty of Medicine in the 2021-2022 academic year. A survey including students’ sociodemographic characteristics and distance education perspective was applied to collect data. The data were evaluated with statistical analysis. Results: Of the participating students, 85 were in 4th-grade, 157 were in 5th-grade, 79 were 6th-grade medical students. Answers to the question “If there was a second choice, would you choose the faculty of medicine?” 119 stated that they would choose the medical faculty again, 102 stated that they would not, and 100 stated that they were undecided. Answers to the question “What is your preferred education system option from today” 17 of the students preferred only the online education system, 127 only the face-to-face education system, and 177 preferred the system with online and face-to-face education have stated. Conclusion: In terms of students’ answers to the survey, it was seen that their level of perspective on distance education was undecided and it was determined that many factors affected distance education satisfaction. As a result, medical faculty students’ anxiety increased during the pandemic period and they were less satisfied with the distance education system.